The Effectiveness of Mindfulness-Based Relapse Prevention on Chinese Methamphetamine Dependent Patients: A Pilot Study - Zhai, Jing; Long, Yan; Shi, Jingqing; Shi, Daqing; Ren, Qihuan; Zhao, Min; Du, Jiang (Frontiers in Psychiatry, 2022)
Methamphetamine use is a serious problem in China. Compulsory isolation detoxification is the main treatment measure for drug dependents, whereas psychological interventions in compulsory isolation detoxification centers are extremely inadequate. The current study aimed to examine the effects of mindfulness-based relapse prevention (MBRP) on methamphetamine dependence patients in Chinese compulsory isolation detoxification treatment institutions. 41 methamphetamine dependent patients received 16-sessions of MBRP in 8 weeks and assessments were conducted at the baseline, 4-week, 8-week (after the whole intervention). Results of repeated measured ANOVAs showed there was no significant effect on emotions and cravings. Findings indicated that the effects of MBRP are still difficult to make firm conclusions due to the insignificant results. Future studies should modify the MBRP and ensure that it is suitable for compulsory isolation detoxification treatment institutions in China.